Computational approaches to biochemical reactivity - Náray-Szabó, Gábor; Warshel, Arieh (Understanding chemical reactivity ;, 2002)
This book summarises recent results in the rapidly developing discipline of the computational aspects of biochemical reactivity. It presents a comprehensive and critical treatise on the subject, with numerous references covering practically all relevant and recent work. The chapters, written by eminent experts in the field, deal with quantum mechanical models for reactions in solution, ab initio molecular orbital studies on enzymatic reactions, combined quantum-classical models for proteins, force field approaches for modelling enzymes, electrostatic effects in proteins, electrostatic basis of enzyme catalysis, the mechanism of proteases, modelling of proton transfer reactions in enzymes and protein-ligand interactions. Audience: This volume will be of interest to graduate students and researchers working in molecular biophysics, structural biology or structure-based molecular design.